Lutein as a natural carotenoid source: Effect on growth, survival and skin pigmentation of goldfish juveniles (Carassius auratus) - Besen K.P.* (2019)
© 2019 John Wiley & Sons LtdThis study aimed to evaluate the effect of lutein supplementation on growth, survival and skin pigmentation for goldfish juveniles. Four diets enriched with different carotenoid sources (lutein, astaxanthin, canthaxanthin and a combination of lutein and canthaxanthin) were compared to a control diet without carotenoid supplementation. The carotenoid inclusion level was standardized at 50 mg kg-1 in all treatments. 240 goldfish juveniles (1.070.57 g) were cultivated in 30 aquariums (30L) during 84 days. The experimental design was completely randomized with five treatments and six replicates. The dietary inclusion of carotenoid pigments did not affect the growth and feeding efficiency of goldfish juveniles. Supplementation with lutein presented higher survival values when compared to the other treatments. Astaxanthin and canthaxanthin supplementation increased the concentration of carotenoids on the skin of goldfish juveniles in relation to the control treatment. For the fish fed with the diet containing lutein, the skin pigmentation was as efficient as astaxanthin and canthaxanthin, but did not differ from the control and combined treatment (canthaxanthin + lutein). The lutein supplementation (50 mg kg-1) improved survival and promoted efficient carotenoid pigmentation on the skin of goldfish juveniles.